Deriving nouns from numerals - Kocijan, Kristina; Librenjak, Sara; Dovedan Han, Zdravko (2011)
The paper discusses formation of numeral nouns in Croatian language using NooJ morphological grammars. Description of this semantic group using productive morphology in NooJ is important in order to minimize the number of unnecessary entries to the dictionary, thus saving on space and time. Numeral nouns in Croatian language can be considered as a specific group of words since they possess a limited number of semantic roots (numeral part) and their endings are from the finite number of suffixes. Syntactically, they are used mostly in the same manner as nouns. We believe that detailed description of numeral nouns will increase both precision and recall in recognition of noun phrases <NP> and prepositional phrases <PP>. This will be demonstrated by reapplying the local grammars for recognition of <NP> and <PP> chunks to the corpus.
Projekt MZOS
ENG